Method for evaluating stress cracking resistance of abs resin

By performing pre-treatment and multiple tests on ABS resin, the problem of time-consuming and labor-intensive evaluation in the existing technology has been solved, realizing a rapid and accurate evaluation of stress cracking resistance performance, providing a quantitative evaluation method, and guiding the improvement of ABS resin.

CN122361075APending Publication Date: 2026-07-10PETROCHINA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510036978.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2026-07-10

Smart Images

  • Figure CN122361075A_ABST
    Figure CN122361075A_ABST
Patent Text Reader

Abstract

This invention relates to the field of ABS resin and discloses a method for evaluating the stress cracking resistance of ABS resin. The method includes: melting ABS resin to obtain a melt, followed by ultrasonic irradiation and granulation; obtaining the tensile properties, melt flow index, and viscosity-to-shear rate parameters of the ABS resin before and after treatment; and obtaining an evaluation value for the stress cracking resistance of the ABS resin based on these parameters. This evaluation method is time-saving and labor-saving. Furthermore, by utilizing external stimuli to "stimulate" and "intervene" the molecular chain structure and microstructure of the ABS resin, the obtained test data more accurately reflect the molecular chain structure and microstructure information of the ABS resin, thus leading to a more accurate evaluation result for the stress cracking resistance of the ABS resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ABS resin technology, and more specifically to a method for evaluating the stress cracking resistance of ABS resin. Background Technology

[0002] ABS resin is a plastic with excellent comprehensive performance, with good surface gloss, excellent mechanical properties, easy surface spraying and electroplating properties, and is therefore widely used in the manufacture of electronic appliances, automobiles and other consumer goods and industrial products.

[0003] The presence of highly polar polyacrylonitrile components and the rubber phase, while imparting excellent performance characteristics to ABS resin, also reduces its melt flowability. Furthermore, the high glass transition temperature of polyacrylonitrile makes ABS resin prone to residual stress during manufacturing. Over long-term use, this residual stress can lead to silver streaks, coating peeling, or cracking, significantly impacting product durability and performance stability. Therefore, improving the stress cracking resistance of ABS resin is crucial, and testing and evaluating this resistance is an essential prerequisite for achieving such improvements.

[0004] Currently, aging tests are generally used to test and evaluate the stress cracking resistance of ABS resin. However, this testing method not only requires processing a large number of samples, but also requires a long aging period, which is time-consuming and labor-intensive. Summary of the Invention

[0005] The purpose of this invention is to overcome the problem of time-consuming and laborious evaluation of the stress cracking resistance of ABS resin in the prior art, and to provide a method for evaluating the stress cracking resistance of ABS resin.

[0006] To achieve the above objectives, the present invention provides a method for evaluating the stress cracking resistance of ABS resin, comprising:

[0007] The ABS resin is subjected to a pre-treatment process, which includes: melting the ABS resin to obtain a corresponding melt, subjecting the melt to ultrasonic irradiation, and granulating the ultrasonically irradiated melt.

[0008] Tensile properties were tested on ABS resin without the pre-treatment and ABS resin with the pre-treatment, and their respective tensile property parameters were obtained. Melt flow properties were tested on ABS resin without the pre-treatment and ABS resin with the pre-treatment, and their respective melt flow indexes were obtained. Rheological tests were conducted on ABS resin without the pre-treatment and ABS resin with the pre-treatment, and their respective viscosity-shear rate parameters were obtained.

[0009] Based on their respective tensile property parameters, melt flow index, and viscosity-shear rate parameters, the stress cracking resistance of ABS resin is evaluated.

[0010] In this embodiment of the application, the preset treatment further includes: mixing ABS and additives before melting the ABS resin;

[0011] The additives include at least one of styrene-acrylonitrile copolymer, PEG-acrylonitrile copolymer, PEG resin, polyolefin wax, white oil, stearate, fatty acid derivative, fluoropolymer, polydimethylsiloxane, and polyisobutylene.

[0012] In the embodiments of this application, the amount of additive added is 0.01%-15% of the ABS resin by weight percentage.

[0013] In the embodiments of this application, the amount of additive added is 0.05%-5% of the ABS resin by weight percentage.

[0014] In this embodiment of the application, a twin-screw extruder is used to melt ABS resin and then extrude it to obtain the corresponding melt.

[0015] In this embodiment of the application, the length-to-diameter ratio of the twin-screw extruder is (6-36):1;

[0016] The extrusion temperature of the twin-screw extruder is 160℃-240℃;

[0017] The speed of the twin-screw extruder is 2 rpm to 100 rpm;

[0018] The twin-screw extruder performs 1-3 extrusions.

[0019] In this embodiment of the application, the length-to-diameter ratio of the twin-screw extruder is (18-24):1;

[0020] The extrusion temperature of the twin-screw extruder is 200℃-210℃;

[0021] The twin-screw extruder operates at speeds of 8 rpm to 30 rpm.

[0022] The twin-screw extruder performs one extrusion cycle.

[0023] In this embodiment, an ultrasonic generator installed at the outlet section of a twin-screw extruder is used to ultrasonically irradiate the melt.

[0024] In the embodiments of this application, the power of ultrasonic irradiation is 50W-500W.

[0025] In the embodiments of this application, the power of ultrasonic irradiation is 150W-250W.

[0026] In the embodiments of this application, the tensile performance parameters include tensile strength and elongation at break.

[0027] In this embodiment of the application, obtaining the respective corresponding melt flow index includes:

[0028] The melt flow index of the ABS resin without the preset treatment under the second load is obtained, and the melt flow index of the ABS resin after the preset treatment under the first load and the second load is obtained, wherein the first load is less than the second load.

[0029] In this embodiment of the application, the viscosity-shear rate related parameters include the slope of the viscosity-shear rate curve.

[0030] In this embodiment of the application, obtaining the evaluation value of the stress cracking resistance of ABS resin based on its respective tensile property parameters, melt flow index, and viscosity-with-shear rate parameters includes:

[0031] The stress cracking resistance of ABS resin is evaluated based on the tensile strength, elongation at break, melt flow index under the second load, and the slope of the corresponding viscosity-shear rate curve of the ABS resin without the pre-treatment, as well as the tensile strength, elongation at break, melt flow index under the first load, melt flow index under the second load, and the slope of the corresponding viscosity-shear rate curve of the ABS resin after the pre-treatment.

[0032] In this embodiment, the evaluation value of the stress cracking resistance of ABS resin is calculated based on the following formula:

[0033]

[0034] Among them, R crac k is the evaluation value for the stress cracking resistance of ABS resin; T s0 T represents the tensile strength of the ABS resin without the aforementioned pre-treatment, in MPa; l0 represents the elongation at break of the ABS resin without the aforementioned pre-treatment; T sM1 is the tensile strength of the ABS resin after the pre-treatment, in MPa; M2 is the elongation at break of the ABS resin after the pre-treatment; M3 is the melt flow index of the ABS resin after the pre-treatment under the first load, in g / 10min; M4 is the melt flow index of the ABS resin after the pre-treatment under the second load, in g / 10min; M5 is the tensile strength of the ABS resin after the pre-treatment under the second load, in g / 10min. 20 , where is the melt flow index of the untreated ABS resin under the second load, in g / 10min; k0 is the slope of the viscosity-shear rate curve of the untreated ABS resin; and k is the slope of the viscosity-shear rate curve of the treated ABS resin.

[0035] The above technical solution includes: pre-treating ABS resin, the pre-treating process including: melting ABS resin to obtain a corresponding melt, subjecting the melt to ultrasonic irradiation, and granulating the ultrasonically irradiated melt; performing tensile property tests on ABS resin without the pre-treating process and ABS resin with the pre-treating process to obtain their respective tensile property parameters; performing melt flow property tests on ABS resin without the pre-treating process and ABS resin with the pre-treating process to obtain their respective melt flow indexes; performing rheological tests on ABS resin without the pre-treating process and ABS resin with the pre-treating process to obtain their respective viscosity-to-shear rate parameters; and obtaining an evaluation value for the stress cracking resistance of ABS resin based on its respective tensile property parameters, its respective melt flow index, and its respective viscosity-to-shear rate parameters. On the one hand, the solution provided in this application is time-saving and labor-saving; on the other hand, by using external stimuli (including shear force and heat during melt extrusion, adding additives, applying ultrasonic irradiation, etc.) to "stimulate" and "intervene" the molecular chain structure and micro-phase morphology of ABS resin, the obtained tensile property parameters, melt flow index and rheological law can more accurately reflect the information of the molecular chain structure and micro-phase morphology of ABS resin, and thus the evaluation results of the stress cracking resistance of ABS resin are more accurate.

[0036] Other features and advantages of the embodiments of this application will be described in detail in the following detailed description section. Attached Figure Description

[0037] The accompanying drawings are provided to further illustrate the embodiments of this application and form part of the specification. They are used together with the following detailed description to explain the embodiments of this application, but do not constitute a limitation on the embodiments of this application. In the drawings:

[0038] Figure 1The illustration shows a flowchart of a method for evaluating the stress cracking resistance of ABS resin according to an embodiment of this application. Detailed Implementation

[0039] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are only for illustration and explanation of the embodiments of this application and are not intended to limit the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0040] It should be noted that if the embodiments of this application involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a certain specific posture (as shown in the figure). If the specific posture changes, the directional indicators will also change accordingly.

[0041] Furthermore, if the embodiments of this application involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, features defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the technical solutions of various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. If the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed in this application.

[0042] As described in the background section, ABS resin is a plastic with excellent comprehensive performance, possessing good surface gloss, superior mechanical properties, easy surface coating, and electroplating capabilities. Therefore, it is widely used in the manufacture of consumer goods and industrial products such as electronics, automobiles, and more. While the presence of highly polar polyacrylonitrile components and the rubber phase imparts excellent performance characteristics to ABS resin, it also reduces its melt flowability. Furthermore, the high glass transition temperature of polyacrylonitrile leads to the generation of residual stress during the manufacturing process. Over long-term use, this residual stress can further cause silver streaks, coating peeling, or cracking in ABS resin products, significantly impacting their durability and performance stability. Therefore, improving the stress cracking resistance of ABS resin is of great significance, and testing and evaluating its stress cracking resistance is a crucial prerequisite for achieving this improvement. The stress cracking resistance of ABS resin mainly includes two aspects: firstly, the ease with which residual stress is generated, which is generally determined by the molecular structure, microstructure, and processing of the ABS resin; secondly, the ability to withstand residual stress, which is closely related to the molecular chain structure and microstructure of the ABS resin. These two aspects together constitute the stress cracking resistance of ABS resin and are two important aspects for evaluating its stress cracking performance. Currently, aging tests are generally used to test the stress cracking resistance of ABS resin. However, this testing method requires processing a large number of samples and a long aging period, which is time-consuming and labor-intensive. Overall, there is currently no unified standard or efficient testing method; most testing methods are time-consuming and labor-intensive, and the results are greatly affected by sample preparation and aging conditions, making direct results difficult to obtain.

[0043] Next, evaluate the stress cracking resistance of ABS resin raw materials.

[0044] To address this, one embodiment of this application provides a method for evaluating the stress cracking resistance of ABS resin, such as... Figure 1 As shown, the method for evaluating the stress cracking resistance of ABS resin may include the following steps:

[0045] Step 101: Perform a pre-treatment on the ABS resin, the pre-treatment including: melting the ABS resin to obtain a corresponding melt, subjecting the melt to ultrasonic irradiation, and granulating the ultrasonically irradiated melt.

[0046] To ensure more accurate subsequent evaluation, the pre-treatment may further include: mixing the ABS resin and additives before melting the ABS resin, specifically through physical mixing. Then, melting the ABS resin specifically involves melting the mixture obtained from mixing the ABS resin and additives.

[0047] In practical implementation, additives with good processing fluidity and certain compatibility with both SAN resin and the rubber phase PB are preferred. Simultaneously, the compatibility of the additive with SAN resin and the rubber phase PB should not be too good or too bad; otherwise, it will result in good compatibility with only one phase while failing to balance the other phase, leading to inaccurate subsequent evaluations. In the embodiments of this application, the additive may include at least one of styrene-acrylonitrile copolymer, PEG-acrylonitrile copolymer, PEG resin, polyolefin wax, white oil, stearate, fatty acid derivative, fluoropolymer, polydimethylsiloxane, and polyisobutylene. Furthermore, the amount of additive added, by weight percentage, is 0.01%-15% of the ABS resin; for example, it can be 0.01%, 1%, 5%, 10%, 15%, or any percentage between the listed percentages. More preferably, the amount of additive added, by weight percentage, is 0.05%-5% of the ABS resin.

[0048] When additives are added to ABS resin, they can migrate to the phase interface during subsequent extrusion. At the same time, due to the good processing fluidity of the additives, the molecular structure and phase morphology of ABS resin are more likely to change under the influence of the additives and the subsequent external processing environment. This allows subsequent testing methods to reveal its resistance to residual stress cracking.

[0049] In this embodiment, a twin-screw extruder can be used to melt ABS resin and then extrude it to obtain the corresponding melt. It is understood that when ABS resin and additives are mixed, the twin-screw extruder...

[0050] The object melt-extruded by the bar extruder is a mixture of ABS resin and additives.

[0051] In practical implementation, the length-to-diameter ratio of the twin-screw extruder can be (6-36):1; for example, it can be 6:1, 10:1, 20:1, 30:1, 36:1, or any ratio between these listed proportions. The extrusion temperature of the twin-screw extruder can be 160℃-240℃; for example, it can be 160℃, 180℃, 200℃, 220℃, 240℃, or any temperature between these listed temperatures. The rotational speed of the twin-screw extruder can be 2rpm-100rpm; for example, it can be 2rpm, 30rpm, 50rpm, 80rpm, 100rpm, or any rotational speed between these listed speeds. The number of extrusion passes of the twin-screw extruder can be 1-3; for example, it can be 1, 2, or 3 times. More preferably, the length-to-diameter ratio of the twin-screw extruder is (18-24):1; the extrusion temperature of the twin-screw extruder is 200℃-210℃; the rotational speed of the twin-screw extruder is 8rpm-30rpm; and the number of extrusion cycles of the twin-screw extruder is 1.

[0052] In this embodiment, an ultrasonic generator can be installed at the outlet section of a twin-screw extruder to apply ultrasonic irradiation to the melt.

[0053] In practice, the power of ultrasonic irradiation can be 50W-500W; for example, it can be 50W, 100W, 200W, 400W, 500W, or any power between the listed powers. More preferably, the power of ultrasonic irradiation is 150W-250W.

[0054] By performing melt extrusion and ultrasonic irradiation on the melt, ABS resin can be subjected to shearing, vibration and cavitation under a high temperature field, making it easier for the molecular structure and phase morphology of ABS resin to change under the influence of the external processing environment, so that subsequent tests can better evaluate its stress cracking resistance.

[0055] In this embodiment, the granulation process may include water cooling, stringing, granulation, and drying. That is, the melt after ultrasonic irradiation is sequentially subjected to water cooling, stringing, granulation, and drying.

[0056] Step 102: Perform tensile property tests on the ABS resin without the pre-treatment and the ABS resin with the pre-treatment, and obtain their respective tensile property parameters; perform melt flow property tests on the ABS resin without the pre-treatment and the ABS resin with the pre-treatment, and obtain their respective melt flow indices; perform melt flow property tests on the ABS resin without the pre-treatment and the ABS resin with the pre-treatment, and obtain their respective melt flow indices; perform melt flow property tests on the ABS resin without the pre-treatment and the ABS resin with the pre-treatment.

[0057] Rheological tests were conducted on the ABS resin that underwent the pre-treatment to obtain the corresponding viscosity parameters as a function of shear rate.

[0058] The tensile properties parameters may include tensile strength and elongation at break; that is, the tensile properties parameters of the ABS resin without the pre-treatment include tensile strength and elongation at break, and the tensile properties parameters of the ABS resin after the pre-treatment include tensile strength and elongation at break.

[0059] In practice, the tensile properties of ABS resin without the pre-treatment and ABS resin with the pre-treatment can be tested according to the national standard GBT 1040.4-2006, which specifies the method for determining the tensile properties of plastics.

[0060] In this embodiment of the application, the corresponding melt flow indexes are obtained respectively, including: obtaining the melt flow index of ABS resin without the preset treatment under a second load, and obtaining the melt flow index of ABS resin after the preset treatment under a first load and a second load. The first load is less than the second load; specifically, the first load can be 2.16 kg, and the second load can be 5 kg.

[0061] In practice, melt flow performance tests can be performed on ABS resin that has not undergone the aforementioned pre-treatment and ABS resin that has undergone the aforementioned pre-treatment, in accordance with the national standard GBT 3682-2018.

[0062] In this embodiment of the application, the viscosity-shear rate related parameters may include the slope of the viscosity-shear rate curve; that is, the slope of the viscosity-shear rate curve for ABS resin without the preset treatment and the slope of the viscosity-shear rate curve for ABS resin after the preset treatment are obtained respectively.

[0063] The viscosity-shear rate curves of ABS resin without the pre-treatment and ABS resin with the pre-treatment can be measured using a high-pressure capillary rheometer. Then, the slopes of each curve can be obtained through mathematical fitting analysis.

[0064] In practice, rheological tests can be performed on ABS resins that have not undergone the aforementioned pretreatment and ABS resins that have undergone the aforementioned pretreatment in accordance with ISO 11443 (2005-3-1).

[0065] Step 103: Based on their respective tensile property parameters, melt flow index, and viscosity-with-shear rate parameters, the evaluation value of the stress cracking resistance of ABS resin is obtained.

[0066] That is, the evaluation value of the stress cracking resistance of ABS resin is obtained based on the tensile strength, elongation at break, melt flow index under the second load, and the slope of the corresponding viscosity-shear rate curve of the ABS resin without the pre-treatment, and the tensile strength, elongation at break, melt flow index under the first load, melt flow index under the second load, and the slope of the corresponding viscosity-shear rate curve of the ABS resin after the pre-treatment.

[0067] Specifically, the stress cracking resistance evaluation value of ABS resin can be calculated based on the following formula (1):

[0068]

[0069] In the above formula (1), R crac k is the evaluation value for the stress cracking resistance of ABS resin, which is dimensionless; T s0 The tensile strength of the ABS resin without the aforementioned pre-treatment is expressed in MPa; l0 represents the elongation at break of the ABS resin without the aforementioned pre-treatment, in %; T s M1 represents the tensile strength of the ABS resin after the pre-treatment, in MPa; M2 represents the elongation at break of the ABS resin after the pre-treatment, in %; M3 represents the melt flow index of the ABS resin after the pre-treatment under the first load, in g / 10min; M4 represents the melt flow index of the ABS resin after the pre-treatment under the second load, in g / 10min; M5 represents the elongation at break of the ABS resin after the pre-treatment. 20 , where is the melt flow index of the untreated ABS resin under the second load, in g / 10min; k0 is the slope of the viscosity-shear rate curve of the untreated ABS resin, dimensionless; k is the slope of the viscosity-shear rate curve of the treated ABS resin, dimensionless.

[0070] Among them, the stress cracking resistance evaluation value R of ABS resin crack The larger the value, the better the resistance to stress cracking.

[0071] The better.

[0072] It is understood that the method for evaluating the stress cracking resistance of ABS resin provided in this application includes: pre-treating the ABS resin, wherein the pre-treating includes: melting the ABS resin to obtain a corresponding melt, subjecting the melt to ultrasonic irradiation, and granulating the ultrasonically irradiated melt; performing tensile property tests on the ABS resin without the pre-treating and the ABS resin after the pre-treating, respectively obtaining their respective tensile property parameters; performing melt flow property tests on the ABS resin without the pre-treating and the ABS resin after the pre-treating, respectively obtaining their respective melt flow index; performing rheological tests on the ABS resin without the pre-treating and the ABS resin after the pre-treating, respectively obtaining their respective viscosity-to-shear rate parameters; and obtaining an evaluation value for the stress cracking resistance of the ABS resin based on its respective tensile property parameters, its respective melt flow index, and its respective viscosity-to-shear rate parameters. On the one hand, the solution provided in this application is time-saving and labor-saving; on the other hand, by utilizing external stimuli (including shear force and heat during melt extrusion, adding additives, applying ultrasonic irradiation, etc.) to "stimulate" and "intervene" the molecular chain structure and micro-phase morphology of ABS resin, the obtained tensile property parameters, melt flow index and rheological laws can more accurately reflect the information of ABS molecular chain structure and micro-phase morphology, and thus the evaluation results of the stress cracking resistance of ABS resin are more accurate.

[0073] Furthermore, the solution provided by the embodiments of this application enables the quantification of the stress cracking resistance of ABS resin, thereby providing effective guidance for improving the stress cracking resistance of ABS resin.

[0074] From the perspective of polymer physics, the generation of residual stress and the resistance to stress cracking are closely related to the molecular structure, microstructure, and processing of ABS resin. Therefore, by appropriately characterizing the molecular structure and microstructure of ABS, it is possible to quantitatively express the ability of ABS resin to generate residual stress and its resistance to stress cracking. Based on this, the inventors proposed the above-mentioned technical solution.

[0075] The solutions provided by the above embodiments of this application will be described below with reference to specific examples.

[0076] It should be understood that the following embodiments are merely specific implementation methods and do not imply any improper limitation on the solution of this application.

[0077] Example 1

[0078] Resin A and Resin B are injection molded parts made of two different ABS resins with different molecular structures. Resin A failed due to stress cracking after 24 months of normal use, while Resin B failed due to stress cracking after 31 months of normal use under the same conditions.

[0079] The stress cracking resistance of raw material resins A and B was evaluated using the following method:

[0080] ① Physically mix resins A and B with the additives respectively; the additives are styrene-acrylonitrile copolymer and PEG-acrylonitrile copolymer. By mass percentage, the amount of styrene-acrylonitrile copolymer added is 0.05% of ABS resin, and the amount of PEG-acrylonitrile copolymer added is 1.75% of ABS resin.

[0081] ② The mixtures corresponding to resin A and resin B obtained in step ① were melted using a twin-screw extruder, and then extruded to obtain the corresponding melts. An ultrasonic generator was used to irradiate each melt at the outlet section of the twin-screw extruder. The irradiated melts were then sequentially subjected to water cooling, stringing, granulation, and drying. The twin-screw extruder had an aspect ratio of 18:1, an extrusion temperature of 190℃, a rotation speed of 80 rpm, and performed two extrusion passes. The ultrasonic irradiation power was 200W.

[0082] ③ Tensile properties were tested on resin A without the above treatment and resin A after the above treatment to obtain their respective tensile strength and elongation at break; tensile properties were tested on resin B without the above treatment and resin B after the above treatment to obtain their respective tensile strength and elongation at break.

[0083] ④ Melt flow properties tests were performed on resin A without the above treatment and resin A after the above treatment. The melt flow index of resin A without the above treatment at a load of 5 kg was obtained, and the melt flow index of resin A after the above treatment at a load of 2.16 kg and a load of 5 kg was obtained, respectively. Melt flow properties tests were also performed on resin B without the above treatment and resin B after the above treatment. The melt flow index of resin B without the above treatment at a load of 5 kg was obtained, and the melt flow index of resin B after the above treatment at a load of 2.16 kg and a load of 5 kg was obtained, respectively.

[0084] The melt flow index of the treated resin B under loads of 2.16 kg and 5 kg is described.

[0085] ⑤ Rheological tests were performed on resin A without the above treatment and resin A after the above treatment using a high-pressure capillary rheometer. The viscosity-shear rate curves for resin A without the above treatment were obtained, and the slope of the curves was obtained through mathematical fitting analysis. The viscosity-shear rate curves for resin A after the above treatment were also obtained, and the slope of the curves was obtained through mathematical fitting analysis. Rheological tests were performed on resin B without the above treatment and resin B after the above treatment using a high-pressure capillary rheometer. The viscosity-shear rate curves for resin B without the above treatment were obtained, and the slope of the curves was obtained through mathematical fitting analysis. The viscosity-shear rate curves for resin B after the above treatment were also obtained, and the slope of the curves was obtained through mathematical fitting analysis.

[0086] The corresponding numerical results of the above tests are shown in Table 1.

[0087] ⑥ Calculate the stress cracking resistance evaluation value R corresponding to resin A and resin B based on the above formula (1). crack The R values ​​for resins A and B were calculated. crack The values ​​are 308.86 and 533.36 respectively. Judging from the magnitude of the values, the evaluation results are positively correlated with their actual service time, which is consistent with the trend of stress cracking resistance performance during actual service time.

[0088] Example 2

[0089] Resin C and Resin D are microporous foamed parts made of two different ABS resins with different molecular structures. Resin C failed due to stress cracking after 12 months of normal use, while Resin D failed due to stress cracking after 13 months of use under the same conditions.

[0090] The stress cracking resistance of raw material resins C and D was evaluated using the following method:

[0091] ① Physically mix resins C and D with the additives respectively; the additive is white oil, and the amount of white oil added is 4.5% of the ABS resin by mass percentage.

[0092] ② The mixtures corresponding to resin C and resin D obtained in step ① are melted using a twin-screw extruder, and then extruded to obtain the corresponding melts. An ultrasonic generator is used to apply ultrasonic irradiation to each melt at the outlet section of the twin-screw extruder. Then, the ultrasonically irradiated melts are processed according to…

[0093] The process involves water cooling, stringing, granulation, and drying. The twin-screw extruder has a length-to-diameter ratio of 20:1, an extrusion temperature of 210℃, a rotation speed of 30 rpm, and undergoes one extrusion cycle. The ultrasonic irradiation power is 150W.

[0094] ③ Tensile properties were tested on resin C without the above treatment and resin C after the above treatment to obtain their respective tensile strength and elongation at break; tensile properties were tested on resin D without the above treatment and resin D after the above treatment to obtain their respective tensile strength and elongation at break.

[0095] ④ Melt flow properties were tested on resin C without the above treatment and resin C with the above treatment. The melt flow index of resin C without the above treatment under a load of 5 kg was obtained, and the melt flow index of resin C with the above treatment under a load of 2.16 kg and a load of 5 kg was obtained. Melt flow properties were tested on resin D without the above treatment and resin D with the above treatment. The melt flow index of resin D without the above treatment under a load of 5 kg was obtained, and the melt flow index of resin D with the above treatment under a load of 2.16 kg and a load of 5 kg was obtained.

[0096] ⑤ Rheological tests were performed on untreated resin C and treated resin C using a high-pressure capillary rheometer. The viscosity-shear rate curves for untreated resin C were obtained, and the slope of the curves was obtained through mathematical fitting analysis. The viscosity-shear rate curves for treated resin C were also obtained, and the slope of the curves was obtained through mathematical fitting analysis. Rheological tests were performed on untreated resin D and treated resin D using a high-pressure capillary rheometer. The viscosity-shear rate curves for untreated resin D were obtained, and the slope of the curves was obtained through mathematical fitting analysis. The viscosity-shear rate curves for treated resin D were also obtained, and the slope of the curves was obtained through mathematical fitting analysis.

[0097] The corresponding numerical results of the above tests are shown in Table 1.

[0098] ⑥ Calculate the stress cracking resistance evaluation value R corresponding to resin C and resin D based on the above formula (1). crack The R values ​​for resins C and D were calculated. crack The values ​​are 358.75 and 378.95 respectively, from the data...

[0099] The value can be used to determine the evaluation result, which is positively correlated with its actual service time and consistent with the pattern of stress cracking resistance during actual service time.

[0100] Example 3

[0101] Resin E and Resin F are extruded parts made from two different ABS resins with different molecular structures. Resin E failed due to stress cracking after 20 months of normal use, while Resin F failed due to stress cracking after 7 months of use under the same conditions.

[0102] The stress cracking resistance of raw material resins E and F was evaluated using the following method:

[0103] ① Physically mix resins E and F with the additives respectively; the additives are polydimethylsiloxane and PEG-acrylonitrile copolymer. By mass percentage, the amount of polydimethylsiloxane added is 1% of the ABS resin, and the amount of PEG-acrylonitrile copolymer added is 0.35% of the ABS resin.

[0104] ② The mixtures corresponding to resin E and resin F obtained in step ① were melted using a twin-screw extruder, and then extruded to obtain the corresponding melts. An ultrasonic generator was used to irradiate each melt at the outlet section of the twin-screw extruder. The irradiated melts were then sequentially subjected to water cooling, stringing, granulation, and drying. The twin-screw extruder had a length-to-diameter ratio of 24:1, an extrusion temperature of 200℃, a rotation speed of 8 rpm, and performed three extrusion passes. The ultrasonic irradiation power was 250W.

[0105] ③ Tensile properties were tested on resin E without the above treatment and resin E after the above treatment to obtain their respective tensile strength and elongation at break; tensile properties were tested on resin F without the above treatment and resin F after the above treatment to obtain their respective tensile strength and elongation at break.

[0106] ④ Melt flow properties were tested on resin E without the above treatment and resin E with the above treatment. The melt flow index of resin E without the above treatment under a load of 5 kg was obtained, and the melt flow index of resin E with the above treatment under a load of 2.16 kg and a load of 5 kg was obtained. Melt flow properties were tested on resin F without the above treatment and resin F with the above treatment. The melt flow index of resin F without the above treatment under a load of 5 kg was obtained, and the melt flow index of resin F with the above treatment under a load of 2.16 kg and a load of 5 kg was obtained.

[0107] ⑤ Rheological tests were performed on resin E without the above treatment and resin E after the above treatment using a high-pressure capillary rheometer. The viscosity-shear rate curves for resin E without the above treatment were obtained, and the slope of the curves was obtained through mathematical fitting analysis. The viscosity-shear rate curves for resin E after the above treatment were also obtained, and the slope of the curves was obtained through mathematical fitting analysis. Rheological tests were performed on resin F without the above treatment and resin F after the above treatment using a high-pressure capillary rheometer. The viscosity-shear rate curves for resin F without the above treatment were obtained, and the slope of the curves was obtained through mathematical fitting analysis. The viscosity-shear rate curves for resin F after the above treatment were also obtained, and the slope of the curves was obtained through mathematical fitting analysis.

[0108] The corresponding numerical results of the above tests are shown in Table 1.

[0109] ⑥ Calculate the stress cracking resistance evaluation value R corresponding to resin E and resin F based on the above formula (1). crack The R values ​​of resin E and resin F were calculated. crack The values ​​are 355.83 and 54.99, respectively. Judging from the magnitude of the values, the evaluation results are positively correlated with their actual service time, which is consistent with the trend of stress cracking resistance performance during actual service time.

[0110] Example 4

[0111] Resin G and Resin H are blown film parts made from two different ABS resins with different molecular structures. Resin G failed due to stress cracking after 5 months of normal use, while Resin H failed due to stress cracking after 11 months of use under the same conditions.

[0112] The stress cracking resistance of raw material resins G and H was evaluated using the following method:

[0113] ① Physically mix resins G and H with the additives respectively; the additive is polyisobutylene, and the amount of polyisobutylene added is 0.1% of the ABS resin by mass percentage.

[0114] ② The mixtures corresponding to resin G and resin H obtained in step ① are melted using a twin-screw extruder, and then extruded to obtain the corresponding melts. Each melt is then subjected to ultrasonic irradiation using an ultrasonic generator at the outlet section of the twin-screw extruder. The ultrasonically irradiated melts are then sequentially subjected to water cooling, stringing, granulation, and drying. The twin-screw extruder has a length-to-diameter ratio of 30:1, an extrusion temperature of 190℃, a rotation speed of 60 rpm, and performs one extrusion cycle. The ultrasonic irradiation power is 50W.

[0115] ③ Tensile properties were tested on resin G without the above treatment and resin G after the above treatment to obtain their respective tensile strength and elongation at break; tensile properties were tested on resin H without the above treatment and resin H after the above treatment to obtain their respective tensile strength and elongation at break.

[0116] ④ Melt flow properties were tested on resin G without the above treatment and resin G with the above treatment. The melt flow index of resin G without the above treatment under a load of 5 kg was obtained, and the melt flow index of resin G with the above treatment under a load of 2.16 kg and a load of 5 kg was obtained. Melt flow properties were tested on resin H without the above treatment and resin H with the above treatment. The melt flow index of resin H without the above treatment under a load of 5 kg was obtained, and the melt flow index of resin H with the above treatment under a load of 2.16 kg and a load of 5 kg was obtained.

[0117] ⑤ Rheological tests were performed on untreated resin G and treated resin G using a high-pressure capillary rheometer. The viscosity-shear rate curves for untreated resin G were obtained, and the slope of the curves was obtained through mathematical fitting analysis. The viscosity-shear rate curves for treated resin G were also obtained, and the slope of the curves was obtained through mathematical fitting analysis. Rheological tests were performed on untreated resin H and treated resin H using a high-pressure capillary rheometer. The viscosity-shear rate curves for untreated resin H were obtained, and the slope of the curves was obtained through mathematical fitting analysis. The viscosity-shear rate curves for treated resin H were also obtained, and the slope of the curves was obtained through mathematical fitting analysis.

[0118] The corresponding numerical results of the above tests are shown in Table 1.

[0119] ⑥ Calculate the stress cracking resistance evaluation value R corresponding to resin G and resin H based on the above formula (1). crac k. The R values ​​of resin G and resin H are calculated. crac The k values ​​are 168.19 and 366.27, respectively. Judging from the numerical values, the evaluation results are positively correlated with their actual service time, which is consistent with the trend of stress cracking resistance performance during actual service time.

[0120] Example 5

[0121] Resin I and Resin J are calendered parts made of two different ABS resins with different molecular structures. Resin I failed due to stress cracking after 60 months of normal use, while Resin J failed due to stress cracking after 8 months of use under the same conditions.

[0122] The stress cracking resistance of raw material resins I and J was evaluated using the following method:

[0123] ①Resins I and J are physically mixed with the additives respectively; the additives are polyethylene paraffin oil, and the amount of polyisobutylene added is 3.3% by mass percentage.

[0124] ② The mixtures corresponding to resin I and resin J obtained in step ① were melted using a twin-screw extruder, and then extruded to obtain the corresponding melts. An ultrasonic generator was used to irradiate each melt at the outlet section of the twin-screw extruder. The irradiated melts were then sequentially subjected to water cooling, stringing, granulation, and drying. The twin-screw extruder had a length-to-diameter ratio of 24:1, an extrusion temperature of 240℃, a rotation speed of 57 rpm, and performed two extrusion passes. The ultrasonic irradiation power was 450 W.

[0125] ③ Tensile properties were tested on resin I without the above treatment and resin I with the above treatment to obtain their respective tensile strength and elongation at break; tensile properties were tested on resin J without the above treatment and resin J with the above treatment to obtain their respective tensile strength and elongation at break.

[0126] ④ Melt flow properties were tested on resin I without the above treatment and resin I with the above treatment. The melt flow index of resin I without the above treatment under a load of 5 kg was obtained, and the melt flow index of resin I with the above treatment under a load of 2.16 kg and a load of 5 kg was obtained. Melt flow properties were tested on resin J without the above treatment and resin J with the above treatment. The melt flow index of resin J without the above treatment under a load of 5 kg was obtained, and the melt flow index of resin J with the above treatment under a load of 2.16 kg and a load of 5 kg was obtained.

[0127] ⑤ Rheological tests were performed on resin I without the above treatment and resin I after the above treatment using a high-pressure capillary rheometer. The viscosity-shear rate curves for resin I without the above treatment were obtained, and the slope of the curves was obtained through mathematical fitting analysis. The viscosity-shear rate curves for resin I after the above treatment were also obtained, and the slope of the curves was obtained through mathematical fitting analysis. Rheological tests were performed on resin J without the above treatment and resin J after the above treatment using a high-pressure capillary rheometer. The viscosity-shear rate curves for resin J without the above treatment were obtained, and the slope of the curves was obtained through mathematical fitting analysis. The viscosity-shear rate curves for resin J after the above treatment were also obtained, and the slope of the curves was obtained through mathematical fitting analysis.

[0128] The corresponding numerical results of the above tests are shown in Table 1.

[0129] ⑥ Calculate the stress cracking resistance evaluation value R corresponding to resin I and resin J based on the above formula (1). crack The R values ​​of resins I and J were calculated. crack The values ​​are 1213.7 and 201.0 respectively. Judging from the magnitude of the values, the evaluation results are positively correlated with their actual service time, which is consistent with the trend of stress cracking resistance performance during actual service time.

[0130] Table 1 Test Data

[0131]

[0132] Therefore, the solution provided in this application can accurately evaluate the stress cracking resistance of ABS resin, which is consistent with the stress cracking resistance of ABS resin in actual use.

[0133] It should also be noted that the endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0134] The terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus. Without further limitation, an element defined by the phrase “comprising one…” does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.

[0135] The above are merely embodiments of this application and are not intended to limit the scope of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of the claims of this application.

Claims

1. A method for evaluating the stress cracking resistance of ABS resin, characterized in that, The evaluation methods include: The ABS resin is subjected to a pre-treatment process, which includes: melting the ABS resin to obtain a corresponding melt, subjecting the melt to ultrasonic irradiation, and granulating the ultrasonically irradiated melt. Tensile properties were tested on ABS resin without the pre-treatment and ABS resin with the pre-treatment, and their respective tensile property parameters were obtained. Melt flow properties were tested on ABS resin without the pre-treatment and ABS resin with the pre-treatment, and their respective melt flow indexes were obtained. Rheological tests were conducted on ABS resin without the pre-treatment and ABS resin with the pre-treatment, and their respective viscosity-shear rate parameters were obtained. Based on their respective tensile property parameters, melt flow index, and viscosity-shear rate parameters, the stress cracking resistance of ABS resin is evaluated.

2. The method for evaluating the stress cracking resistance of ABS resin according to claim 1, characterized in that, The pre-treatment also includes: mixing ABS and additives before melting the ABS resin; The additives include at least one of styrene-acrylonitrile copolymer, PEG-acrylonitrile copolymer, PEG resin, polyolefin wax, white oil, stearate, fatty acid derivative, fluoropolymer, polydimethylsiloxane, and polyisobutylene.

3. The method for evaluating the stress cracking resistance of ABS resin according to claim 2, characterized in that, The amount of additives added is 0.01%-15% of the ABS resin by weight percentage.

4. The method for evaluating the stress cracking resistance of ABS resin according to claim 3, characterized in that, The amount of additives added is 0.05%-5% of the ABS resin by weight percentage.

5. The method for evaluating the stress cracking resistance of ABS resin according to claim 1, characterized in that, The ABS resin is melted using a twin-screw extruder and then extruded to obtain the corresponding melt.

6. The method for evaluating the stress cracking resistance of ABS resin according to claim 5, characterized in that, The length-to-diameter ratio of the twin-screw extruder is (6-36):1; The extrusion temperature of the twin-screw extruder is 160℃-240℃; The speed of the twin-screw extruder is 2 rpm to 100 rpm; The twin-screw extruder performs 1-3 extrusions.

7. The method for evaluating the stress cracking resistance of ABS resin according to claim 6, characterized in that, The length-to-diameter ratio of the twin-screw extruder is (18-24):1; The extrusion temperature of the twin-screw extruder is 200℃-210℃; The twin-screw extruder operates at speeds of 8 rpm to 30 rpm. The twin-screw extruder performs one extrusion cycle.

8. The method for evaluating the stress cracking resistance of ABS resin according to claim 5, characterized in that, The melt is ultrasonically irradiated using an ultrasonic generator installed at the outlet section of a twin-screw extruder.

9. The method for evaluating the stress cracking resistance of ABS resin according to claim 8, characterized in that, The power of ultrasonic irradiation is 50W-500W.

10. The method for evaluating the stress cracking resistance of ABS resin according to claim 9, characterized in that, The power of ultrasonic irradiation is 150W-250W.

11. The method for evaluating the stress cracking resistance of ABS resin according to claim 1, characterized in that, The tensile properties include tensile strength and elongation at break.

12. The method for evaluating the stress cracking resistance of ABS resin according to claim 11, characterized in that, The process of obtaining their respective melt flow indices includes: The melt flow index of the ABS resin without the preset treatment under the second load is obtained, and the melt flow index of the ABS resin after the preset treatment under the first load and the second load is obtained, wherein the first load is less than the second load.

13. The method for evaluating the stress cracking resistance of ABS resin according to claim 12, characterized in that, The parameters related to viscosity as a function of shear rate include the slope of the viscosity-shear rate curve.

14. The method for evaluating the stress cracking resistance of ABS resin according to claim 13, characterized in that, The evaluation value of the stress cracking resistance of ABS resin is obtained based on its respective tensile property parameters, melt flow index, and viscosity-with-shear rate parameters, including: The stress cracking resistance of ABS resin is evaluated based on the tensile strength, elongation at break, melt flow index under the second load, and the slope of the corresponding viscosity-shear rate curve of the ABS resin without the pre-treatment, and the tensile strength, elongation at break, melt flow index under the first load, melt flow index under the second load, and the slope of the corresponding viscosity-shear rate curve of the ABS resin after the pre-treatment.

15. The method for evaluating the stress cracking resistance of ABS resin according to claim 14, characterized in that, The evaluation value of the stress cracking resistance of ABS resin is calculated based on the following formula: Among them, R crack T represents the stress cracking resistance evaluation value of ABS resin. s0 T represents the tensile strength of the ABS resin without the aforementioned pre-treatment, in MPa; l0 represents the elongation at break of the ABS resin without the aforementioned pre-treatment; T s M1 is the tensile strength of the ABS resin after the pre-treatment, in MPa; M2 is the elongation at break of the ABS resin after the pre-treatment; M3 is the melt flow index of the ABS resin after the pre-treatment under the first load, in g / 10min; M4 is the melt flow index of the ABS resin after the pre-treatment under the second load, in g / 10min; M5 is the tensile strength of the ABS resin after the pre-treatment under the second load, in g / 10min. 20 , where is the melt flow index of the untreated ABS resin under the second load, in g / 10min; k0 is the slope of the viscosity-shear rate curve of the untreated ABS resin; and k is the slope of the viscosity-shear rate curve of the treated ABS resin.